EFFECT OF PAD WARM FOR PREVENTION HYPOTHERMIA IN NEWBORN AT THE HOUSEHOLD LEVEL AT KABUPATEN KARAWANG - Warliana, Warliana; Solihah, Eneng (Indonesian Journal of Adult and Community Education, 2022)
Background: The body temperature of newborns is very vulnerable to changes in room temperature, especially during the first day of birth and the neonatal period. Baby care has an important role in ensuring the stability of body temperature during the adaptation period. Prevention of hypothermia in newborns aims to maintain a stable body temperature by avoiding exposure to cold and wind. Most parachute materials contain plastic, the basic ingredients of which are polyester, which have the properties of a waterproof and heat-resistant material, often used as a material for warm jackets in cold climates because of its ability to withstand the wind. Research objective: to determine the effect of a Padwarm or warm sleeping bag in preventing hypothermia in normal newborns. Method: this type of research is Quasy Experiment with the design "One group pre test-post test design" the study sample is 35 normal newborns. The sampling technique is accidental sampling, the analytical test used is the Wilcoxon Signed Rank Test. Results: there is a significant difference between before using Padwarm and after using Padwarm where the average temperature before use was 36.26°C; 95% CI (36.21 -36.31) and the average temperature after use was 36.709°C; 95% CI ( 36.652 -36.765) p value of 0.000. Suggestion: Padwarm warm sleeping bags can be an alternative choice for baby sleeping bags in early neonates.